Evaluasi Dukungan Implementasi Sistem Informasi Untuk Pengembangan 6-Area Smart City - Handrie Noprisson (JSAI (Journal Scientific and Applied Informatics), 2023)
Information systems play an important role in supporting smart cities. Through this, the concept of information systems integrating information and communication technology (ICT) is implemented to improve efficiency, quality of life, and environmental sustainability. The study aims to find out research data on the use of systems in smart city development. This study used Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) as a guideline for conducting literature reviews. The selected research data is data published around 2011 to 2022 that is eligible based on data on the Google Scholar scientific database. From the article data analyzed, it is known that existing IS research to support smart cities is E-Business, E-Commerce, E-Government (E3) as many as 15 research data. The categories of E-Business, E-Commerce, E-Government (E3) are the core of smart cities that support urban activities in general. Furthermore, the System for Different Management Groups (MG) category was discussed as many as 13 research data. The System for Linking the Enterprise (LE) category is discussed by 3 studies. E-business supports smart cities by enabling efficient retail and delivery methods, increasing electronic participation, and facilitating safe energy trade whereas E-government can support smart cities by promoting services.